Immigrants' Leisure Participation and Acculturative Stress Management: The Mediating Effect of Community Embeddedness (Global Journal of Human-Social Science, 2020)
The increasing trend of migration has driven studies from multiple perspectives, including the conceptual lens of their mobility and professional activities. Another important dimension of immigrants' settlement is the role of leisure participation. One issue in immigrants' settlement is acculturative stress, an issue related to the difficulties immigrants face in their adjustment to the lifestyle of their host country. This paper explores the role of leisure participation by investigating a mediating effect of community embeddedness which assists immigrants to manage acculturative stress. Community embeddedness enables immigrants to adjust and develop emotional and functional connections to their new community and fosters their social integration. This mediator is likely to be related to leisure participation. Mediated regression analysis confirmed that leisure participation lessened two components of acculturative stress; immigrants' not feeling at home and perceived discrimination when mediated by community embeddedness.
Keywords: leisure participation; immigrants; acculturative stress; community embeddedness